Engle & Granger cointegration test for GDP and public consumption in the Republic of North Macedonia - Zoran Ivanovski; Nadica Ivanovska; Vesna Korunovska (UTMS Journal of Economics, 2022)
In this paper, we test cointegration between GDP and Public consumption of the Republic of North Macedonia, for quarterly data of twenty years' time series (2000Q1-2019Q4). We present results of two methods for cointegration test: first, residual regression test table and second, Engle & Granger cointegration test and Philips Ouliaris test. Both methods provides same conclusions. We did not find the presence of spurious regression. ADF Unit Root Test on residuals confirms that residuals are not stationary and that series are not cointegrated. Engle-Granger cointegration test and Phillips Ouliaris cointegration test results confirms that GDP and Public consumption of the Republic of North Macedonia are not cointegrated and can be used for further analyze using VAR(p) model...
Keywords: C1; C32; C35; 330; cointegration; VAR; stationarity; public consumption; probability